The prevalence of dental caries and associated factors among students living with disability in the Amhara region, Ethiopia. Issue 6 (15th August 2022) - Tefera, Amare T.; Girma, Biruk; Adane, Aynishet; Muche, Abebe; Ayele, Tadesse A.; Getahun, Kefyalew A.; Aniley, Zelallem; Ali, Semira; Handebo, Simegnew
Abstract: Objectives: People living with disability are more vulnerable to dental caries and have a high decayed, missed, and filled permanent teeth (DMFT) index and untreated dental disease than nondisabled individuals. In Ethiopia, there is a dearth of information on the oral health status of the disabled population. Hence, this study aimed to determine the prevalence of dental caries and its predictors among special needs school students in the Amhara region, Ethiopia. Methods: An institution‐based cross‐sectional study was done on special needs school students in the Amhara region from November 2020 to April 2021. The study participants were recruited using a simple random sampling technique using a computer random generator. Data collection was done using the World Health Organization oral health survey tool. Data entry was done using Epi‐data 4.6 and analyzed using SPSS 26. A logistic regression model was used to identify the possible predictors of dental caries. Results: Four hundred and forty‐three students with a mean age of 15.8 ± 3.8 were included in the study. The prevalence of dental caries was 41.5% (95% confidence interval [CI]: 36.3, 46.0) in permanent dentition with a mean DMFT score of 1.3 ± 1.6. The prevalence of dental caries in primary dentition was 23.1% (95% CI: 11.9, 32.1) with a mean decayed, missed, and filled primary teeth (dmft) score of 1.9 ± 0.2. Being 7–12 years old (adjusted odds ratios [AOR] = 3.6, 95% CI: 1.6, 8.3), lower grade level (AOR = 2.4, 95% CI:1.3, 4.4), poor oral hygiene status (AOR = 2.5, 95% CI: 1.3, 4.8), and lack of parental support during tooth brushing (AOR = 2.2, 95% CI: 1.2, 4.1) were independent predictors of dental caries. Conclusions: A significant amount of special needs school students in the study area had dental caries. Age, grade level, oral hygiene status, and lack of parent support during tooth brushing were independent predictors of dental caries.